1991
DOI: 10.1007/bf00202512
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal baclofen infusion in patients with spasticity and neurogenic bladder disease

Abstract: Summary.Nine severely spastic men suffering from neurogenic bladder disease secondary to spinal cord lesion or multiple sclerosis were treated with continuous intrathecal infusion of baclofen using an implanted programmable pump. Bladder function improved in all patients. Significant improvements consisted of an increase in bladder capacity, a decrease in residual volume and a diminution of pelvic floor spasms. Three patients became continent. Intermittent self-catheterization was no longer impeded by adductor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Kums and Delhaas reported nine cases (three multiple sclerosis [MS] and six SCI) with increased bladder capacity, a decrease in residual volume, and diminished pelvic floor spasm after ITB therapy. Three patients become continent (5). Steers et al reported ten patients (SCI, MS, syrinx, hereditary spastic paraplegia [HSP]), after ITB therapy, had resolution of "irritative" voiding and urge incontinence of the uninhibited bladder.…”
Section: Discussionmentioning
confidence: 99%
“…Kums and Delhaas reported nine cases (three multiple sclerosis [MS] and six SCI) with increased bladder capacity, a decrease in residual volume, and diminished pelvic floor spasm after ITB therapy. Three patients become continent (5). Steers et al reported ten patients (SCI, MS, syrinx, hereditary spastic paraplegia [HSP]), after ITB therapy, had resolution of "irritative" voiding and urge incontinence of the uninhibited bladder.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies have indicated therapeutic effects on bladder function (20)(21)(22)(23)(24)(25) and activities II daily living (26). Bacl<>t'cn is rapidly becoming the drug of choice for intraspinal antispastic therapy and has recently been approved in several coun, tries for treatment of severe spinal spasticity.…”
Section: Introductionmentioning
confidence: 99%